Assessment of food provider ecosystem services as food security in modern industrial estate planning at Muaro Jambi Regency - Hindayani Purna; Pratama Armandha Redo (E3S Web of Conferences)
This research aims to determine the food carrying capacity and environmental suitability of Kemingking Dalam Village in Muaro Jambi Regency for maintaining food security amidst planned modern industrial developments. Designated as a strategic national area, this village is set to become the first modern industrial zone in Jambi Province. The study employed Geospatial Information System (GIS) methods to assess and map food carrying capacity, particularly focusing on rice production. Findings indicate that the area is currently capable of meeting its food needs.The food provision ecosystem services were categorized into five levels, from very low to very high. The study revealed that 71% (1,874.32 hectares) of the village falls under the “very high” category for food provision. However, a significant portion of the planned industrial area, about 995 hectares or 68.47% of the total, overlaps with these high to very high food provision zones.The policy implication is that areas that have the high-very high category in providing food are not recommended to become modern industrial areas in order to maintain food security.